Biochemical characterization of dipeptidylcarboxypeptidase of Leishmania donovani - Baig, M. S.; Gangwar, S.; Goyal, N. (Cellular and Molecular Biology, 2011)
The incidence of parasitic infection, leishmaniasis, has been steadily increasing worldwide. Since, the existing chemotherapy of these diseases suffers from lack of safe and effective drugs and/or the presence of widespread drug resistance, there is an urgent need for development of potent, mechanism-based anti-parasitic agents. The peptidases of protozoan parasites are becoming increasingly important for their role in parasite survival and pathogenecity. Leishmania donovani dipeptidylcarboxypeptidsae (LdDCP), an angiotensin converting enzyme (ACE) related metallopeptidase has been identified and characterized as a putative drug target for antileishmanial chemotherapy. The kinetic parameters for LdDCP with substrate, Hip-His-Leu were determined as, Km, 4 mM and Vmax, 1.173 µmole/ml/min. The enzyme was more sensitive to 1,10 phenanthroline than EDTA and was 80% inhibited in presence of NaCl. Among various protease inhibitors, pepstatin was found as potent inhibitor of LdDCP.